(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Branding the product and attractingthe trusted and loyal customers are the most important elements in the contemporary marketing strategies. Consumers recollect the brands which provide them unique experiences and satisfaction.Brand Trust is the consumers’ feeling of security, and their readiness to rely on a particular brand.This study examines the influence of brand expectation and brand experience on brand trust and brand loyalty among the customers of high involvement products through a well-structured questionnaire. For these responseswere collected from240 motorcycle owners.non probability sampling namely convenience sampling method in Palakkad District ofKerala.The results derived from descriptive statistics indicate that the customers have high degree of perception inBrand Expectation, Brand Experience which influencethe brand trust and brand loyalty.